The archaeology of medieval Islamic frontiers: from the Mediterranean to the Caspian Sea - Eger, A. Asa (University Press of Colorado, 2019)
Cover -- Title Page -- Copyright Page -- Contents -- 1. The Archaeology of Medieval Islamic Frontiers: An Introduction -- Part I. The Western Frontiers: The Maghrib and The Mediterranean Sea -- 2. Ibāḍī Boundaries and Defense in the Jabal Nafūsa (Libya) -- 3. Guarding a Well-Ordered Space on a Mediterranean Island -- 4. Conceptualizing the Islamic-Byzantine Maritime Frontier -- Part II. The Southern Frontiers: Egypt and Nubia -- 5. Monetization across the Nubian Border: A Hypothetical Model -- 6. The Land of Ṭarī' and Some New Thoughts on Its Location -- Part III. The Eastern Frontiers: The Caucasus and Central Asia -- 7. Overlapping Social and Political Boundaries: Borders of the Sasanian Empire and the Muslim Caliphate in the Caucasus -- 8. Buddhism on the Shores of the Black Sea: The North Caucasus Frontier between the Muslims, Byzantines, and Khazars -- 9. Making Worlds at the Edge of Everywhere: Politics of Place in Medieval Armenia -- About the Authors -- Index.